2018
DOI: 10.1021/acsami.8b10253
|View full text |Cite
|
Sign up to set email alerts
|

Efficiently Improving the Stability of Inverted Perovskite Solar Cells by Employing Polyethylenimine-Modified Carbon Nanotubes as Electrodes

Abstract: Inverted perovskite solar cells (PSCs) have been becoming more and more attractive, owing to their easy-fabrication and suppressed hysteresis, while the ion diffusion between metallic electrode and perovskite layer limit the long-term stability of devices. In this work, we employed a novel polyethylenimine (PEI) modified cross-stacked superaligned carbon nanotube (CSCNT) film in the inverted planar PSCs configurated FTO/NiO /methylammonium lead tri-iodide (MAPbI)/6, 6-phenyl C61-butyric acid methyl ester (PCBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 58 publications
0
60
0
Order By: Relevance
“…Recently, Lin and co‐workers reported that CSCNT:PEI‐based device obtained outstanding stability, sustaining over 94% of original efficiencies after 500 h storage in ambient air and 90% of that after 500 h thermal treatment at 60 °C. The devices also showed good stability exposed to moisture under thermal stress (60 °C, 60% RH), remaining over 70% of original PCEs after 500 h, which could be further raised to 85% while encapsulating the devices with PMMA layer …”
Section: Instability Of Phtotoactive Layer Of Pscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lin and co‐workers reported that CSCNT:PEI‐based device obtained outstanding stability, sustaining over 94% of original efficiencies after 500 h storage in ambient air and 90% of that after 500 h thermal treatment at 60 °C. The devices also showed good stability exposed to moisture under thermal stress (60 °C, 60% RH), remaining over 70% of original PCEs after 500 h, which could be further raised to 85% while encapsulating the devices with PMMA layer …”
Section: Instability Of Phtotoactive Layer Of Pscsmentioning
confidence: 99%
“…CNT films used as back contact have been reported in conventional PSCs but rarely in inverted PSCs . Zhou et al employed a novel poly ethyleneimine (PEI)‐modified cross‐stacked super‐aligned carbon nanotube (CSCNT) film in the inverted planar PSCs . CSCNT:PEI‐based inverted PSCs show superior durability.…”
Section: Structural Influence On the Stability Of Pscsmentioning
confidence: 99%
“…As in the case of graphite and carbon black back electrodes, organic [227][228][229] and inorganic 149 HTMs have been exploited to further increase the hole extraction ability of CNTs. 230,231 Aitola et al reported a CNT-based PSC with spiro-OMeTAD as the HTM.…”
Section: Carbon Nanotube-based Back Electrodesmentioning
confidence: 99%
“…A similar strategy involves the use of poly(ethylenimine) (PEI) in the CNT film. 229 PEI played the important role of ameliorating the interface between carbon and PC 61 BM, the latter being used as an electron acceptor in inverted FTO/NiO/CH 3 NH 3 PbI 3 / PC 61 BM/CNTs:PEI architectures. The beneficial effect of PEI was demonstrated by the dramatic increase in PCE, i.e.…”
Section: Carbon Nanotube-based Back Electrodesmentioning
confidence: 99%
“…Now the production at an industrial level is being discussed based on its high PCE, yet there are number of imminent problems to address before commercialization. [153] Conventional metal electrodes have problems of oxidation, ion migration, and poor barrier-ability, let alone the expensive material cost and deposition cost. According to literatures, [99,152] the conventional transparent electrode ITO is the sole layer that limits the flexible application as they cause crack under severe bending cycle.…”
Section: Lead Organohalide Perovskite Solar Cellsmentioning
confidence: 99%